2012
DOI: 10.1371/journal.pone.0033663
|View full text |Cite
|
Sign up to set email alerts
|

Mirna Expression Profiles Identify Drivers in Colorectal and Pancreatic Cancers

Abstract: Background and AimAltered expression of microRNAs (miRNAs) hallmarks many cancer types. The study of the associations of miRNA expression profile and cancer phenotype could help identify the links between deregulation of miRNA expression and oncogenic pathways.MethodsExpression profiling of 866 human miRNAs in 19 colorectal and 17 pancreatic cancers and in matched adjacent normal tissues was investigated. Classical paired t-test and random forest analyses were applied to identify miRNAs associated with tissue-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 27 publications
7
88
0
1
Order By: Relevance
“…The study by Mar-Aguilar et al confirmed the upregulation of miR-382 in the serum of patients with breast cancer; a sensitivity of 94.40% and a specificity of 90.00% was found for the diagnosis of breast cancer (24). A study by Li et al showed that miR-382-5p expression was significantly downregulated in patients with ductal carcinoma in situ (25), while miR-1246 was demonstrated to exhibit high expression in colorectal cancer (26), esophageal squamous cell carcinoma (27), cervical carcinoma (28), hepatocellular carcinoma (29) and other cancers. The expression profiles of miRNAs in the serum and tissues are different.…”
Section: A B C Dmentioning
confidence: 92%
“…The study by Mar-Aguilar et al confirmed the upregulation of miR-382 in the serum of patients with breast cancer; a sensitivity of 94.40% and a specificity of 90.00% was found for the diagnosis of breast cancer (24). A study by Li et al showed that miR-382-5p expression was significantly downregulated in patients with ductal carcinoma in situ (25), while miR-1246 was demonstrated to exhibit high expression in colorectal cancer (26), esophageal squamous cell carcinoma (27), cervical carcinoma (28), hepatocellular carcinoma (29) and other cancers. The expression profiles of miRNAs in the serum and tissues are different.…”
Section: A B C Dmentioning
confidence: 92%
“…Gene expression profiling has already demonstrated its effectiveness at subtyping various cancers, however miRNA profiles are equally discriminatory and can even be more informative, as changes in their expression can provide insights into the myriad of gene permutations observed in various cancer subtypes: links have indeed been made between misregulated miRNAs and the target genes that are affected, thus unraveling some of the unique gene networks involved [117]. miRNA profiles may identify cancer-specific signatures distinguishing between normal and cancerous tissue [118][119][120][121], but they can also discriminate different subtypes of a particular cancer [119,122,123].…”
Section: Mirnas As Prognostic Biomarkersmentioning
confidence: 99%
“…A total of 25% of patients with colorectal cancer have a genetic history, which is associated with familial adenomatous polyposis and hereditary non-polyposis colorectal cancer (7). Results of molecular pathology and colorectal cancer expression profile chip screening have demonstrated that multiple genes serve regulatory roles in the processes of colorectal cancer development (8). In order to identify possible gene target therapies and individualized treatments, various studies have focused on genes associated with the pathogenesis of colorectal cancer and their mechanisms.…”
Section: Introductionmentioning
confidence: 99%